Oblique Turnover Flap for Repositioning and Flattening of the Lateral Crura: A Novel Technique to Manage Cephalic Malposition of Lower Lateral Cartilage - Goksel, Abdulkadir; Vladykina, Elena (Facial Plastic Surgery, 2017)
Malposition of the lower lateral cartilage (LLC) is a relatively common anatomical variation, described as any displacement of the lateral crura from the usual parallel direction with the nostril rims. Cephalic malpositioned LLC has the following characteristics: abnormal axes of the lateral crura, bulbous and broad nasal tip, parenthesis deformity, long alar creases, alar wall hollows, nostril deformities, and incompetence of the external valve. Numerous techniques were founded to correct this aesthetic and functional unpleasant variation, although all of them have some limitations. The authors described and evaluated the efficacy of the oblique turnover flap (OTOF) technique in the management of cephalic malposition of LLC (CMLLC). The advantages of this technique are: it does not need any additional grafting; it is quick and safe to perform; it has stable results. In the present study, 24 primary rhinoplasties using OTOF technique were performed between January 2014 and September 2016. There were 21 females (87.5%) and 3 males (12.5%), with age ranging from 23 to 46 years. The mean follow-up period was 12.1 months (range: 8–28 months). All patients were treated by the senior author (A.G.) in the RinoIstanbul Clinic. Three parameters were measured and compared pre- and postoperatively, using a t-test and a p value criteria of 0.05. The difference was found to be statistically significant: the angle between the central axis of the lateral crura and the septum on each side, satisfaction scale rating of the patients' nasal tip appearance and the satisfaction scale rating of patients' nose breathing. The angle of the central axis of lateral cruras to the midline significantly increased, the mean satisfactory scale ratings of nasal tip appearance and breathing quality were also significantly improved. OTOF is a quick, useful, efficient technique for repositioning and flattening of the lateral cruras of CMLLC with a good, predictable, and stable long-term results in our hands if used on right candidates.
Keywords: cephalic malposition of lower lateral cartilage; oblique turnover flap; nasal tip contouring; bulbous tip; rhinoplasty